Evaluation of the Effects of Different Therapeutic Agents on Experimental Dry Eye (DE) for the Purpose of Ocular Surface Impairments in Mice - Kulualp, Kadri; Kilic, Servet (Medwell Online, 2012)
Dry Eye Syndrome (DES) may impair ocular surface integrity, damaging corneal and conjunctival epithelial cells which play an important role on ocular surface health. The present study intended to evaluate the effects of different therapeutic agents on ocular surface impairments in Experimental Dry Eye Model. In the study, 112 BALB-C breed female mice were allocated equally as well as randomly to two groups, Control (Cont.) and Experimental (Exp.) with 8 subgroups within themselves. Cont. and Exp. subgroups were called as Formal Saline (SF), Sodium Hyaluronate (SH), Diclofenac Sodium (DS), Olopatadine (O), Retinoic Acid (RA), Fluoromethanole (FML), Cyclosporine-A (CsA) an Doxycycline Hyclate (DH) according to agents administrated. Exp. groups were kept in dry eye cabinet, Cont. groups were maintained at room conditions during 6 weeks. While all animals received no agents between 0 (baseline) e) to 2 weeks, above mentioned agents were administrated topically to their right eyes twice a day, 5 mu L per time between 2-6 weeks. The effects of these agents were evaluated at the 0, 2, 4 and 6 weeks in terms of corneal fluorescein staining and clearance as well as impression cytology and additionally on the 6 weeks with regard to corneal fluorescein permeability. The difference between Cont. and Exp. groups as regards corneal fluorescein and clearance in. g impression cytology were determined as non-significant (p>0.05) for 0 week (baseline) however, it was significant (p<0.05) for 2, 4 and 6 weeks (p<0.05). When the therapeutics were evaluated to all parameters considering variables such as subgroups and measuring times, CsA in terms of corneal fluorescein and permeability and DS in terms of tear clearance and impression cytology were detected to be the most effective agents. In conclusion, it was determined that ocular surface impairment caused by DES may be markedly prevented by immunomodulator efficacious CsA and anti-inflammatory efficacious DS.
Keywords: Mice; evaporative dry eye; diagnosis; treatment; fluorescein; Turkey